Preparing young people for future decision-making about cancer risk in families affected or at risk from hereditary breast cancer: A qualitative interview study. (December 2016) - Rowland, Emma; Plumridge, Gill; Considine, Anna-Marie; Metcalfe, Alison
Abstract: Purpose: Women carrying the mutated BRCA gene, have approximately an 80% life-time risk of developing breast cancer with 50% risk of their children inheriting the gene mutation. Many parents find it difficult to know when and how to disclose this information to their children and how such disclosure might affect their child's future decision-making. Method: This study explored the communication of genetic risk information in families using qualitative semi-structured interviews conducted with parents, children (7–11years) and young people (12–18years) affected or at risk from a BRCA gene mutation. Thematic analysis was applied to coded transcripts producing four themes; family communication, perception of cancer risks, risk management strategies and impact of genetic risk communication in children and young people's decision making. Results: Twenty-seven individuals from 11 families took part, recruited through purposive sampling techniques. Cancer risk caused by a BRCA gene mutation induced a sense of fear in parents about their children's future. As a result, parents with hereditary breast cancer disclosed limited information about the risks associated with prophylactic surgery and/or the psychological and emotional impacts of surgery on body image. This had implications to children and young people's perceptions of prophylactic procedures, which were already influenced by cultural understandings of the 'desirable body' and increasing acceptance and proliferation cosmetic surgery. Conclusion: Lack of risk management information and the acculturation of cosmetic surgery combined to limit children and young people's understanding of the impact of hereditary breast cancer; reducing their ability to actualise the physiological, psychological and emotional consequences of surgery. Highlights: Good communication of genetic risk information strengthens parent/child relationships and encourages coping strategies. Parents can have difficulty tailoring genetic risk information to their child's age, gender, development stage and maturity. Parents communicate risk management strategies such as prophylactic surgeries in a positive manner to their children. The normalisation of cosmetic procedures influences children's perceptions of surgical risk and prophylactic procedures. Positive disclosure of prophylactic procedures and normalisation of cosmetic surgery has led to a desire for genetic testing.